The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1103/physreva.96.021601
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional repulsive Fermi gas in a tunable periodic potential

Abstract: By using unbiased continuos-space quantum Monte Carlo simulations, we investigate the ground state properties of a one-dimensional repulsive Fermi gas subjected to a commensurate periodic optical lattice (OL) of arbitrary intensity. The equation of state and the magnetic structure factor are determined as a function of the interaction strength and of the OL intensity. In the weak OL limit, Yang's theory for the energy of a homogeneous Fermi gas is recovered. In the opposite limit (deep OL), we analyze the conv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…In particular, we have shown that the double occupancy, which is experimentally accessible with cold-atom systems, is a key quantity to investigate phase separation and the formation of different ferromagnetic phases. Our findings can serve as a guide for future cold-atom experiments focussing on itinerant ferromagnetism in one-dimensional optical lattices with p-wave resonant interactions, and they complement previous studies on anti-ferromagnetic correlations in optical lattices [10,[48][49][50].…”
Section: Discussionsupporting
confidence: 80%
“…In particular, we have shown that the double occupancy, which is experimentally accessible with cold-atom systems, is a key quantity to investigate phase separation and the formation of different ferromagnetic phases. Our findings can serve as a guide for future cold-atom experiments focussing on itinerant ferromagnetism in one-dimensional optical lattices with p-wave resonant interactions, and they complement previous studies on anti-ferromagnetic correlations in optical lattices [10,[48][49][50].…”
Section: Discussionsupporting
confidence: 80%
“…It is worth emphasizing that, as opposed to the Aubry-André model -for which all eigenstates localize at the same quasi-disorder strength-in the continuousspace model of Eq. ( 1) the critical quasi-disorder strength depends on the energy of the state [26][27][28]39]. In particular, the low energy eigenstates localize at weaker quasidisorder strength compared to high energy states.…”
Section: Resultsmentioning
confidence: 99%
“…We focus on a halffilled lattice, with N ↑ = N ↓ = 72 particles (unless otherwise specified), so that on average there is one fermion per well of the short-period lattice. It has been recently shown that, in a single half-filled OL, interparticle interactions play an important role, causing the formation of quasi long-range antiferromagnetic order [39]. It is also worth emphasizing that a system comprising N = 144 fermions cannot be addressed via exact diagonalization calculations (see, e.g., the Krylov subspace technique of Ref.…”
Section: Methodsmentioning
confidence: 99%
“…We consider a cluster to be in an insulating state when there is a set of at least three consecutive sites for which κ i =0 [25]. According to equation (11), this means an array of sites for which the population is the same. That set of sites would constitute an insulating domain.…”
Section: Resultsmentioning
confidence: 99%
“…Those systems were traditionally described by the discrete Hubbard model, in which the atoms are confined to the absolute minima of the laser-induced potential wells. This approximation, even though computationally very efficient, is known to break down for shallow optical lattices, both for bosons [10] and fermions [11]. Another possibility is to use the Heisenberg model, also a discrete approximation.…”
Section: Introductionmentioning
confidence: 99%